Running against «Journalist without God»: The Relationship between the Catholic Church in Costa Rica and the Surging of Periodic Confessional Press (1880-1965) - Quesada Rivera, Eugenio (2022)
The objective of this article is to analyze the strategies used by the Catholic Church in Costa Rica as a whole towards their goal of developing a confessional journalism between 1880 and 1965. Three sources were used to analyze the Catholic press phenomenon: pontifical and episcopal documents related to the press and journalism as well as issues from confessional newspapers and magazines. It is concluded that the position of priests in Costa Rica remained loyal to all the instructions given by Rome in order to stimulate a truly Catholic journalism, and also that the non—existent separation between Church and State prevented the consolidation of a confessional journal in the country.